Hope to die : a novel - Hunter, Cara (Hunter, Cara. DI Fawley thriller, 2024)
Midnight. A call out to an isolated farm on the outskirts of Oxford. A body shot at point-blank range in the kitchen. It looks like a burglary gone wrong, but DC Adam Fawley suspects there's something more to it. When the police discover a connection to a high-profile case from years ago, involving a child's murder and an alleged miscarriage of justice, the press go wild. Suddenly Fawley's team are under more scrutiny than ever before. And when you dig up the past, you're sure to find a few skeletons ...